St. Mark 16.1–8 - Cranfield, C. E. B. (Scottish journal of theology, 1952)
The first question that must be considered is the historical one: Was the tomb empty? In a very useful chapter entitled ‘History and Criticism’ Professor A. M. Ramsey discusses ‘some of the types of conclusion reached by those who have applied the methods of critical science to the narratives of the Resurrection’. He mentions first the subjective-vision theory, according to which ‘the appearances of Jesus recorded in the Gospels were simply visions generated by the imaginations of the disciples out of an intense state of emotion or expectancy’. Some who have held this view have combined with it a belief in the survival of Jesus' soul. As Professor Ramsey points out, there are obvious difficulties in the way of accepting this theory—particularly the fact that the disciples' slowness to believe is a marked feature of the narratives. He then mentions the ‘telegram from heaven’ or what we might call the objective-vision theory (Theodor Keim, B. H. Streeter), according to which ‘the residuum of fact behind the narratives consists not in visions generated by the disciples but in visions imparted by God Himself, so as to assure the disciples that Jesus was alive…’